PERUBAHAN BERAT BADAN, TINGGI BADAN DAN STATUS GIZI ANAK BALITA PADA PEMBERIAN EDUKASI DAN TEPUNG DAUN KELOR - zakaria zakaria; Ramlan Asbar; Retno Sri Lestari; Rosmini Rosmini (Jurusan Gizi Poltekkes Kemenkes Makassar, 2017)
Background: Nutrition problem is a public health problem that the prevention can not be done with medical approach and health service only. Nutrition problem in addition is a syndrome of poverty that closely related to the problem of food security at the household level also concerns aspects of knowledge and behavior that are less supportive of lifestyle. Puskesmas Bulurokeng Makassar City in 2016, reported that there are 45 children under five suffering from malnutrition in Bulurokeng urban village.Objectives: The purpose of community service is to assess the change of body weight (TB), height (TB) and nutritional status of children under five in the education and giving of kelor leaf meal on the daily diet of children under five in Bulurokeng Urban Village in 2016. Number of children target infants as many as 29 children, intervention carried out for 1 month.Results: The number of cadres who participated in education as many as 5 people and 29 mothers who have a toddler. But at the end of the intervention, as many as 25 children under five could be collected for analysis. Kelor flour in children under five showed significant difference of weight gain (p = 0,001), but there was no difference in height change (p = 0,41) before and after intervention. The nutritional status of children under five does not change based on body weight index by age (BB / U), height by age (TB / U) and body weight by height (BB / TB).Conclusions: It takes about 3 months of moringa flour intervention on the child's food menu, in order to appear a significant change in nutritional status in children under five.Keyword: Moringa leaf flour, nutritional status.